BUSINESS STRATEGY FOR CAFE DEVELOPMENT: (A Study on De Classe Gelato & Coffe Blitar City) - Indria Guntarayana; Ama Fauziah (JOSAR (Journal of Students Academic Research), 2019)
This research was conducted with the aim of knowing and understanding the development strategies of the De Classe Gelato & Coffe Blitar-East Java Business. The business development strategy of De Classe Gelato & Coffe Cafe is related to the methods used by the company to gain competitive advantage in each of the company's main businesses. This research was conducted using data processing methods and data analysis consisting of qualitative data analysis. Qualitative analysis is used to determine the company's environment to determine the strengths, weaknesses, opportunities, and threats faced by cafes. The results of this research are De Classe Gelato & Coffe Blitar conducting intensive strategies (market penetration, market development, and product development). 1) Market penetration, the company needs to increase the market share of a product or service through larger marketing efforts. 2) Market development, it needs to add distribution channels such as opening branches. 3) Product development that is increasing sales by increasing or modifying existing products. In addition, it must improve the quality of employees.